Altafsir Al'iishariu Eind Aibn Kathir Rahimah Allah - Bakri Muhammad Bakhit (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2021)
Tafsir (interpretation) becomes famous and classified according to what prevailed in terms of interpretation type. Ibn Kathier’s interpretation is one of the interpretations that depended on statements, but despite this, this book is not devoid of interpretation by opinion, such as indicative interpretation. Therefore, it is important for me to write about this subject with the aim of serving and introducing this interpretation, particularly in this aspect that was not mentioned by the predecessors, and also with the aim of explaining the acceptable type of the indicative interpretation. The reason for choosing this topic is that I did not find anyone who addressed this topic in his definition of this interpretation, as well as my desire to explain Ibn Kathier’s approach, which he adopted it with acceptable Taweel (paraphrasing) and rejected every paraphrasing far from the meaning of the verse. In writing the material for this research, I adopted the inductive and descriptive approaches, dividing its material into two sections. In the first one, I mentioned his replies on the paraphrased interpretations. I concluded to the most important results: namely, his adoption of the indicative interpretation indicates that Ibn Katheer - May God have mercy on him – worked diligently to figure out the meanings of the verses for every righteous path. The second section, in which he adopted the indicative interpretation, gives a model of acceptable interpretation. His rejection of some paraphrased interpretations of the predecessors, indicated his mastering of the subject and his broad knowledge, and that he was visionary critic and did not only dealt with transmission. This approach gives his interpretation great scholarly value